2020
DOI: 10.1111/1750-3841.14962
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, thermal, mechanical, optical, and barrier characterization of chia (Salvia hispanica L.) mucilage‐protein concentrate biodegradable films

Abstract: In this study, the effect of chia mucilage (CM) and protein concentrate (CPC) contents on the physicochemical, thermal, mechanical, and optical characteristics of developed films was evaluated. Films were prepared dissolving CM:CPC mixtures (1% w/v) in seven ratios (0:1, 1:4, 1:2, 1:1, 2:1, 4:1, 1:0). Microstructure of treatments with higher CM revealed the formation of polysaccharide granules. A semicrystalline behavior was manifested in 1:0, which decreased as CPC content in the formulations increased. Conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…The protein content of the degummed and defatted flour obtained from S. hispanica seeds was 75.28 ± 1.08%. The percentage obtained in the present study is higher than the percentage reported by Salazar et al (2020), who despite obtaining a protein concentrate had a lower protein content (40.5 ± 0.5%), probably attributed to differences in the degumming procedure and the additional defatting steps performed in the present study.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…The protein content of the degummed and defatted flour obtained from S. hispanica seeds was 75.28 ± 1.08%. The percentage obtained in the present study is higher than the percentage reported by Salazar et al (2020), who despite obtaining a protein concentrate had a lower protein content (40.5 ± 0.5%), probably attributed to differences in the degumming procedure and the additional defatting steps performed in the present study.…”
Section: Resultscontrasting
confidence: 89%
“…The method reported by Salazar et al. (2020) was followed with some adjustments. The mucilage was extracted by preparing a suspension with whole seeds and distilled water in a 1:40 (w/v) proportion.…”
Section: Methodsmentioning
confidence: 99%
“…The films formed with defatted flour showed lower thickness than films made with chia flour by Dick et al [23] due to the different amounts of CM used in the film formation. The thickness of films made with whole seeds was consistent with those obtained by Muñoz et al [28] and Salazar Vega et al [29] in films made with whole chia seeds. Moreover, comparing the thickness of both films with other polysaccharide films, it was noticed that the values were slightly higher (0.09-0.012 vs. 0.07-0.08 mm) than films made with cress seed gum [30], psyllium seed [31], Balangu seed mucilage [32], and chitosan [26].…”
Section: Moisture Content Water Solubility and Thicknesssupporting
confidence: 89%
“…Thickness determines the technological properties of the films, so its control plays an important role. It has been observed that the main factors modifying film thickness are the amount of plasticizer added to the film [18] and the amount of coating cast [23,29]. Likewise, for its industrial application as a coatings/film, the factors to consider are the immersion time and the number of times the food is immersed.…”
Section: Moisture Content Water Solubility and Thicknessmentioning
confidence: 99%
“…A chia protein concentrate (CPC) was obtained according to Salazar-Vega et al (2020). After the CM extraction, the residual seed material was ground with a laboratory Thomas-Wiley mill (Model 4, Thomas Scientific, USA) and subjected to lipid extraction with n-hexane.…”
Section: Chia Seed By-productsmentioning
confidence: 99%